Impact analysis of "finishing school programmes on VHSE (agri.)" by Kerala Agricultural University (KAU) - Karishma Zen (Department of Agricultural Extension, College of Agriculture, 2018)
The present study entitled ‘Impact analysis of “Finishing school programmes on VHSE (Agri.)’ by Kerala Agricultural University (KAU).” conducted during September 2016–May 2018 focused on effectiveness of Finishing school (FS) programme in terms of entrepreneurial behaviour and managerial efficiency of the respondents, identifying the present status of respondents, the constraints experienced by the respondents and their profile characteristics followed by suggestions for streamlining the project in subsequent years. The study comprised of ninety respondents who successfully completed Finishing school (FS) programme. These respondents were purposively selected from three categories namely self employed, employed and pursuing higher education with more weightage to self employed and employed categories. Another forty respondents who were not exposed to FS training programme were also selected for a comparative study of two dependant variables. Entrepreneurial behaviour with nine components and managerial efficiency with six components were selected as two dependent variables. Fifteen independent variables were selected through judges’ rating. A structured interview schedule was used for data collection. Statistical tools such as, quartile deviation, frequency, percentage analysis, correlation analysis, student’s t-test and Principal Component Analysis were used for analysis. The present status of the respondents who were exposed to FS were identified in three categories i.e self employed, employed and pursuing higher education categories. It was found that 28.88 per cent and 57.77 per cent of respondents were in self employed and employed category respectively where as 13.33 per cent were in higher education category. Based on analysis of data, it was found that 65.55 per cent of respondents who were unexposed to FS training programme and 56.66 per cent of respondents who were exposed to FS training programme were in low and medium entrepreneurial behaviour respectively. Fifty per cent (50%) of respondents who were unexposed to FS training programme and 55.55 per cent of respondents who were exposed to FS were in low and medium managerial efficiency respectively. Result of student t-test revealed that there was a significant difference between the two categories of respondents with respect to dependent variables. The effect of each component of the two dependant variables were studied through Principal Component Analysis. It was revealed that , knowledgeability, innovativeness and risk taking ability contributed to the entrepreneurial behaviour whereas planning ability, supervising ability and organising ability turned out to be the major contributors to managerial efficiency. Majority (82.22 %) of the respondents were in age category of 25 to 35 years, were males (58.89 %), unmarried (60%), having a family income of ₹ 1,25,000 – ₹ 2,25,000 (47.77 %) and belonged to nuclear family (70%). Regarding the parent occupation, 25.56 per cent of respondents’ parents were labourers and 36.66 per cent of respondents preferred entrepreneurship as their career preference. . The correlation between entrepreneurial behaviour and fourteen independent variables revealed that career preferences, organizational relations, mass media utilization, assertiveness, and attitude towards self employment was found to be positive and significantly correlated. In case of managerial efficiency, variables such as age, career preference, organizational relations, mass media utilization, assertiveness, attitude towards self employment and decision making ability was found to be positive and significantly correlated. A gap analysis conducted among the respondents, revealed that lack of handholding support to the trainees for taking up future projects was the major gap. Regarding the constraints, short duration of first phase of training was the major constraint felt by respondents where as the large number of candidates per batch was the major constraint felt by the implementing officials. The programme needs to be more practically oriented to impart skills to the trainees was the major suggestion by the experts. To conclude, it was revealed that there was a significant difference in the entrepreneurial behaviour and managerial efficiency of respondents who were exposed and unexposed to FS programme. Regarding the present status , 28.88 percent and 57.77 percent of respondents were in self employed and employed category respectively. Gap analysis was also conducted to streamline the project in future. Constraints from both the implementing officials and respondents were identified and suggestions were incorporated.